Digital Sexual Health Education for Young Adults (18–35 Years): A Scoping Review Protocol - Sanam Borji‐Navan; Shahrbanoo Salehin; Tahereh Naseri‐BooriAbadi; Shahrbanoo Goli; Mojgan Mirghafourvand (Health Science Reports)
ABSTRACT Background and Aims Young adults is a key stage for sexual development. Digital interventions provide innovative ways to deliver sexual health education to young adults. This scoping review protocol outlines a plan to map the existing literature on digital sexual health education (DSHE) for young adults, focusing on the dimensions and characteristics of these interventions. Methods This scoping review will adhere to a comprehensive 14‐step methodological framework, integrating the established Arksey and O'Malley methodology with enhancements by Tricco and Peters. This review will follow the PRISMA‐ScR guidelines. The study selection process adhered to the PICOS framework. A combination of thesauri and free‐text methods will be employed. Keywords within each concept were connected using the Boolean operator “OR,” whereas different concepts were linked using the operator “AND.” Databases such as Web of Science (ISI), PubMed, Scopus, EMBASE, and the Cochrane Library (CDSR, Central) and search engines such as Google Scholar and Elmnet were utilized. The extracted data will be synthesized and presented using diagrams and tables accompanied by a narrative summary. Discussion This scoping review will provide a valuable synthesis of the current state of DSHE for young adults. The findings are intended to inform the development and implementation of effective DSHE programs by researchers, educators, policymakers, and healthcare providers. Ultimately, this study contributes to a broader effort to improve the sexual health of young adults. Ethical Code IR.SHMU.REC.1403.085.